Item Analysis of English Final Semester Test - Amalia Vidya Maharani; Nur Hidayanto Pancoro Setyo Putro (Indonesian Journal of EFL and Linguistics, 2020)
Numerous studies have been conducted on the item test analysis in English test. However, investigation on the characteristics of a good test of English final semester test is still rare in several districts in East Java. This research sought to examine the quality of the English final semester test in the academic year of 2018/2019 in Ponorogo. A total of 151 samples in the form of students’ answers to the test were analysed based on item difficulty, item discrimination, and distractors’ effectiveness using Quest program. This descriptive quantitative research revealed that the test does not have good proportion among easy, medium, and difficult item. In the item discrimination, the test had 39 excellent items (97.5%) which meant that the test could discriminate among high and low achievers. Besides, the distractors could distract students since there were 32 items (80%) that had effective distractors. The findings of this research provided insights that item analysis became important process in constructing test. It related to find the quality of the test that directly affects the accuracy of students’ score.